Structure and function of the centriole in animal cells: progress and questions. - Lange, B; Gull, K (1996)
The centriole is a well-recognized, yet poorly understood, organelle present in many eukaryotic cells. Despite excellent electron-microscopic descriptions of its basic triplet microtubule structure, almost nothing is known of its specific molecular components. Here, Bodo Lange and Keith Gull survey centriole structure, duplication and maturation within the cell cycle and focus attention on the possible roles and function of centrioles as components of the centrosome in animal cells.